Ultrasound of the Gastrointestinal Tract - Maconi, Giovanni.; Maconi, Giovanni.; Bianchi Porro, Gabriele.; Bianchi Porro, Gabriele. (Diagnostic Imaging, 2007)
Transabdominal ultrasound has become accepted in clinical practice as a primary imaging procedure in the diagnostic work-up and follow-up of various disorders of the gastrointestinal tract. This book provides a comprehensive overview of the use of ultrasound in the imaging of acute and chronic inflammatory conditions of the gastrointestinal tract as well as of neoplastic and infectious diseases. The specific ultrasound features of gastrointestinal disorders are explained, and the value and limits of ultrasound are discussed. Each chapter provides a description of the findings obtained with ultrasound imaging, with inclusion of alternative diagnostic imaging methods for comparative purposes. Specific technical developments and applications of ultrasound relevant to studies of the gastrointestinal tract, such as functional and 3D ultrasound, contrast agents and operative ultrasound, are also discussed. All authors are considered authorities in their specific fields, and the book includes many high-quality illustrations and the most up-to-date information.